IDENTIFIKACIJA KARAKTERISTIČNIH MORFOLOŠKIH SKLOPOVA KOD IGRAČA I IGRAČICA ODBOJKE FORMIRANIH NA OSNOVU POSMATRANIH LONGITUDINALNIH DIMENZIONALNOSTI - Vesna Nemec; Predrag Nemec (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
In this research work of the type ex post facto the subject of the study are selected morphological dimensions. The aim of this investigation is to confirm qualitative and functional connections between selected length measures and formation of model characteristics of volleyball players taken as the model of morphological constitution. The research comprehends five basic and four deduced variables belonging to the subgroup of index of longitudinal dimensions. The deduced variables are obtained by the division of the basic results in accordance with the values of body height. This hypothesis of identification of typical morphological constitution of the volleyball players, based on the examined longitudinal dimensions, was verified on the samples of both male (n - 575) and female (n - 247) volleyball players with the use of combined mathematical and statistical methods.